Реализация ключевых идей и технологий уровневых модульных программ в профессионально-педагогическом образовании ВУЗа и колледжа - Шумейко, Т.С.; Демисенова, Ш.С.; Сатыбалдина, Р. (My University, 2016)
The article deals with the possibility of realization of the basic ideas of leveled modular programs in vocational teacher education. The authors identify three stages of implementation of the Program of additional vocational training of graduate students of universities engaged in teacher training, developed on the basis of level training programs for teaching staff of the Republic of Kazakhstan in conditions of continuing education. The article presents an analysis of the implementation of the ideas of the Program at every stage from the perspective of teachers and students.
Keywords: the ideas of the leveled modular programs; training of the trainers; course «Professional landmarks of the teachers»; teaching practice in college